Kepastian Hukum terhadap Prinsip Fair and Equitable Treatment dalam Perlindungan Investasi Asing di Indonesia: Studi PCA Case No. 2015-40 - Nur Hikmah Damayanti Sunawir (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The principle of Fair and Equitable Treatment is a crucial principle in international investment law that must be upheld by the home country to provide legal certainty to investors. The problem is that, to date, there are no provisions governing the standard application of Fair and Equitable Treatment. Consequently, the limitations of the FET principle in practice often depend heavily on the approach of each international arbitration tribunal in handling a case, leading to a lack of legal certainty. In this paper, the crucial issue to be discussed is how the principle of fair and equitable treatment is applied in PCA Case No. 2015-40, and its impact on guaranteeing legal protection for foreign investment in Indonesia. The research method used is normative juridical, with data collection techniques through literature review. The results indicate that foreign investors have not received legal certainty in Indonesia due to the lack of clear standards regarding Fair and Equitable Treatment.